Parent’s Language Policies and Language Attitudes in The Family - Nupus, Hayati; Riandi, Riandi (Journal of English Education Studies, 2021)
As citizens of Indonesian society, we should maintain the nation's culture, one of which is cultural heritage, namely the local language or language of each family in Indonesia. So that we as the nation's successors continue to take part in the maintenance and preservation of cultural heritage as a reflection of our identity as children of the nation. The relationship in which education in the family is the goal of national education so that the role of various parties is needed, such as; Teachers, government, facilities and infrastructure, and parents. The aims to be reached in writing this research are; the family language policy adopted by parents at home; Languages coexist (or lose, or gain) in their family environment; the efforts do parents make in learning and maintaining language in their homes. This study uses direct observation methods on the research subject, namely parents. The observations were made in the realm of the family (at home). The data obtained is in the form of a list of statements in the form of the respondent's characteristics, the respondent's response. Interviews in the form of questions and answers about language attitudes and assessment of language and language maintenance. The family language policy implemented by parents at home is frequent, meaning that based on the above percentage results, the policy regarding the language used by parents at home shows "Often" with an overall average percentage value of 50% or half of the expected 100% reviewed from the aspect of the language policy adopted; Language beliefs or ideologies, language practice, and language management. This indicates that the language policy adopted at home with the "Frequently" family is used. Meanwhile, based on the above percentage results, the attitude of the language used by the parents at home shows "disagree" with the overall average percentage value of 40% or 100% of the expected. Their efforts are to use the local language at home, equip their children with various sources both print and non-print, and stay in touch with local ethnic groups. To maintain the local language properly, there must be good cooperation between parents, schools, local government, and the community